Rotavirus vaccines: a major impact on public health six years post-licensure - Lima, Alexandre da Costa (2011)
Ministério da Saúde. Secretaria de Vigilância em Saúde. Instituto Evandro Chagas. Ananindeua, PA, Brasil.